Analysis Of Compliance In Taking Anti-Tuberculosis Drug (Oat) On The Success Of Therapy In Drug-Sensitive Tuberculosis Patients At Muhammadiyah Ahmad Dahlan Hospital, Kediri City - Gading Nurantika; Chintia Devientasari; Hanik Maria Dewi; Hanie Kusuma Wardani (Universitas STRADA Indonesia, 2024)
Tuberculosis, also known as